A travessia da teoria da tendência antissocial à prática: uma contribuição psicanalítica - Roxo Junior, Hélio Antonio Anthero (Universidade Federal de São Carlos, 2024)
This research aims to understand the theory of antisocial tendency and to develop a handling proposal for socio-educational care centres. With an important emphasis on the relationship between the mother (environment) and her baby, Winnicott constructed a complex theory on emotional development and antisocial tendency. His vision of psychopathology refers to environmental failures in the phases in which the subject has not yet acquired the capacity to deal with them. Adaptation failures are defined as traumas and can manifest themselves through various dynamics, including antisocial tendencies. In this work, we use Winnicott's main references to understand the type of trauma associated with antisocial tendency and how the author developed his theory. By analysing experiences in the care of young offenders, we seek to bring Winnicott's constructions closer to the Brazilian context and propose a model of environmental adaptation in care institutions capable of building a potential space for creativity and healing.

Cette recherche vise à comprendre la théorie de la tendance antisociale et à développer une proposition de soin chez les centres de soins socio-éducatifs. En accordant une place importante à la relation entre la mère (environnement) et son bébé, Winnicott a construit une théorie complexe sur le développement affectif et à propos de la tendance antisociale. Sa vision de la psychopathologie se réfère aux défaillances de l'environnement dans les phases où le sujet n'a pas encore acquis la capacité d'y faire face. Les échecs d'adaptation sont définis comme des traumatismes et peuvent se manifester à travers diverses dynamiques, y compris les tendances antisociales. Dans ce travail, nous utilisons les principales références de Winnicott pour comprendre le type de traumatisme associé aux tendances antisociales et comment l'auteur a développé sa théorie. En analysant les expériences de soins de jeunes délinquants, nous cherchons à rapprocher les constructions de Winnicott du contexte brésilien et proposons un modèle d'adaptation de l'environnement dans les institutions capable de construire un espace potentiel de créativité et de guérison.
Transposing antisocial tendency theory into practice: a psychoanalytic contribution
Le passage de la théorie des tendances antisociales à la pratique: une contribution psychanalytique
Keywords: Psicanálise; Winnicott; Trauma; Tendência antissocial; Centro de atendimento socioeducativo; Psychoanalysis; Antisocial tendency; Socioeducational centre; Psychanalyse; Traumatisme; Tendance antisociale; Socioéducatif centre; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::DESENVOLVIMENTO SOCIAL E DA PERSONALIDADE